2019
DOI: 10.7554/elife.44161
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary carcinomas depend upon SMARCB1 loss and are sensitive to proteasome inhibition

Abstract: Renal medullary carcinoma (RMC) is a rare and deadly kidney cancer in patients of African descent with sickle cell trait. We have developed faithful patient-derived RMC models and using whole-genome sequencing, we identified loss-of-function intronic fusion events in one SMARCB1 allele with concurrent loss of the other allele. Biochemical and functional characterization of these models revealed that RMC requires the loss of SMARCB1 for survival. Through integration of RNAi and CRISPR-Cas9 loss-of-function gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…3 Furthermore, c-MYC activation by SMARCB1 loss increases proteotoxic stress rendering cells susceptible to perturbation of their proteostatic machinery by proteasome inhibitors such as bortezomib and ixazomib. 6,7 Indeed, RMC cell lines and xenograft models are vulnerable to proteasome inhibitors 6,8 and there is evidence of clinical activity in patients with RMC that is more likely to be potent and durable if proteasome inhibitors are rationally combined with other therapies. 9 We have accordingly activated an ongoing phase II trial (NCT03587662 at clinicaltrials.gov) that targets both replication and proteotoxic stress by combining gemcitabine and doxorubicin with ixazomib ( Figure 1).…”
mentioning
confidence: 99%
“…3 Furthermore, c-MYC activation by SMARCB1 loss increases proteotoxic stress rendering cells susceptible to perturbation of their proteostatic machinery by proteasome inhibitors such as bortezomib and ixazomib. 6,7 Indeed, RMC cell lines and xenograft models are vulnerable to proteasome inhibitors 6,8 and there is evidence of clinical activity in patients with RMC that is more likely to be potent and durable if proteasome inhibitors are rationally combined with other therapies. 9 We have accordingly activated an ongoing phase II trial (NCT03587662 at clinicaltrials.gov) that targets both replication and proteotoxic stress by combining gemcitabine and doxorubicin with ixazomib ( Figure 1).…”
mentioning
confidence: 99%
“…A recent study by Hong et al demonstrated that genes related to the ubiquitin-proteasome system are necessary for the survival of renal medullary carcinoma cells, which share a molecular profile with SMARCB1-deficient cancers [39]. Increased sensitivity to BTZ in renal medullary carcinoma and other SMARCB1-deficient cells, including MRTs (Malignant rhabdoid tumors) and ATRTs, might be dependent on the loss of SMARCB1 [39].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hong et al demonstrated that genes related to the ubiquitin-proteasome system are necessary for the survival of renal medullary carcinoma cells, which share a molecular profile with SMARCB1-deficient cancers [39]. Increased sensitivity to BTZ in renal medullary carcinoma and other SMARCB1-deficient cells, including MRTs (Malignant rhabdoid tumors) and ATRTs, might be dependent on the loss of SMARCB1 [39]. A similar result was observed in SMARCB1-deficient MRT models-loss of SMARCB1 activates unfolded protein response and increases the endoplasmic reticulum stress, leading to enhanced sensitivity of proteasome inhibitors in SMARCB1-deficient MRT [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study of mosaic mouse models with inactivated SMARCB1 demonstrated that SMARCB1-negative tumors such as RMC are vulnerable to proteasome and autophagy blockade [34]. The sensitivity of RMC to proteasome inhibitors was further validated in a study of RMC cell lines [35]. An ongoing trial (NCT03587662) is thus now evaluating the efficacy of ixazomib, a potent proteasome inhibitor, in combination with gemcitabine and doxorubicin in patients with RMC and other SMARCB1-negative kidney malignancies.…”
Section: Kidney Cancer Geneticsmentioning
confidence: 99%